Designing a User-Centered Facial Health Application (Glowessence) with Usability Testing - Anak Agung Adi Wiryya Putra; Kadek Wahyu Santika Putra; Arefcy Theneven Saban (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The study is carried out for developing the UI (User Interface) and UX(UX) of Glowessence App that enables users to determine their skin type and choose suitable facial care treatment for them. UI/UX Design process involves the User-Centered Design (UCD) principle which is primarily based on customer comfort and finding user requirements. In this study, the method adopted is Design Thinking (5 steps) which started from Empath, Define, Ideate, Prototype and Test. A System Usability Scale (SUS) is used during the testing phase to test the app with 29 participants and an average of 87 was scored — which falls into the